1991
DOI: 10.1172/jci115250
|View full text |Cite
|
Sign up to set email alerts
|

Sp alpha V/41: a common spectrin polymorphism at the alpha IV-alpha V domain junction. Relevance to the expression level of hereditary elliptocytosis due to alpha-spectrin variants located in trans.

Abstract: Spectrin a-chain mutants associated with hereditary elliptocytosis are highly variable in their level of expression. It has been assumed that the degree of elliptocytosis can be increased when the spectrin a chain, encoded by the a gene in trans to the variant, is expressed at a low level. We now provide strong evidence for the existence of low-level expression of spectrin a chains. This condition is referred to as the aV/41 polymorphism.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
29
1

Year Published

1995
1995
2006
2006

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(31 citation statements)
references
References 23 publications
1
29
1
Order By: Relevance
“…Hereditary pyropoikilocytosis has been described in a patient presenting a spαI/74 mutation associated in trans with the α LELY allele [27]. However, our study showed that the association of α LELY allele in trans with the spαI/50 L260P substitution did not lead to a pronounced worsening of clinical or laboratory features, although it may induce mild hemolysis.…”
Section: Discussioncontrasting
confidence: 64%
See 1 more Smart Citation
“…Hereditary pyropoikilocytosis has been described in a patient presenting a spαI/74 mutation associated in trans with the α LELY allele [27]. However, our study showed that the association of α LELY allele in trans with the spαI/50 L260P substitution did not lead to a pronounced worsening of clinical or laboratory features, although it may induce mild hemolysis.…”
Section: Discussioncontrasting
confidence: 64%
“…Probably, the mutation in exon 40 has no functional consequence, but causes an increase in the αV 41-kD fragment [27]. On the other hand, the mutation in intron 45 is responsible for the partial skipping of exon 46 during splicing [12].…”
Section: Discussionmentioning
confidence: 99%
“…This dual presentation evokes the involvement of some recurrent aggravating factor. The latter was found and coined allele α LELY [12, 13]. By itself, α LELY remains silent in both the heterozygous and the homozygous states (because of the large excess of α-chains normally synthesized).…”
Section: Hereditary Elliptocytosis and Hereditary Poikilocytosismentioning
confidence: 99%
“…, that affects dimer assembly (Alloisio et al, 1991;Wilmotte et al, 1993;Randon et al, 1994). When this mutation is present along with an elliptocytosis mutation on the same chain, symptoms of the elliptocytosis mutation are often silent or mitigated since the ␣ LELY mutation will decrease incorporation of the mutated chain onto the membrane.…”
Section: Lelymentioning
confidence: 99%